Agile project health indicators Project/Project portfolio Health indicators, frameworks and methods in agile projects. - ESGUERRA, ALEXANDRA (My University, 2019)
Increased amount of complexity in the development of software projects have created the need for new non-traditional methods to run and organize projects. Agile is helping software companies to manage the complexity in their projects and teams to work more effectively towards effective project delivery. However, this methodology also brings uncertainties regarding the ways of working and there is a need for further clarifications and explorations in order to strive towards best practice. Finding accurate ways to ongoing measure the “health” of a project is one central aspect of this. Theory suggests that in order to work agile, one should decrease administrative work in order to help the project have an easy flow. However, the need to still measure end results on projects, is making companies adopt project management methods to work more agile. Having measurements will not only steer the projects towards plan, but it will also help to make more informed predictions of future outcomes. The aim of this master thesis is to suggest what kind of agile Key Performance Indicators are needed in order to measure the health of a project. A total of thirty-four interviews were conducted at different managerial levels in a software company in order to understand their ways of working with project management and agile. Data analysis identified current challenges and expectations for the future. Five different KPI are suggested and those are a combination of agile and non-agile project measurements. In this study, it was found out that the agile adoption in projects and project portfolio is very immature. There are still tension and uncertainties on how to work in agile, certain processes such as the measurements of projects need to be aligned to how agile works and the way it will work in the specific context. Measurements are good to predict the future, however if there is not a commitment from all the levels in the organization, these will not add any value to the projects. Hence commitment, transparency and collaboration among all the levels and in projects is key to have project success.
Keywords: Samhällsbyggnadsteknik; Civil Engineering